Money growth and Malaysian stock prices: A test of policy ineffectiveness proposition - Ghazali, Noor Azlan; Wong, Sen Min (Universiti Utara Malaysia, 2005)
The policy ineffectiveness proposition proposed by Lucas (1972) and Sargent and Wallace (1975) along the rational expectation model is tested in this study. The proposition claims that unanticipated changes in monetary aggregates exert significant influence on real economic activities while anticipated policy is neutral. In line with this, the efficient market hypothesis indicates that in an efficient market share prices incorporate anticipated information instantaneously leaving only the unanticipated components of the information set to affect share prices. We investigate this proposition on the Malaysian stock returns. Specifically the response of share returns toward changes in actual and decomposed (anticipated and unanticipated) growth of monetary aggregate is analysed. The single equation regressions and the system estimation of Vector Autoregressions (VAR) both point toward the validity of the proposition. The results indicate that positive reactions of share returns to actual money growth are due to the unanticipated components. Movement of share prices is neutral with respect to the anticipated monetary growth. The findings generally favour the policy ineffectiveness proposition that leads to an efficient pricing process for Malaysian shares.